Forest Disturbance Feedbacks From Bedrock to Atmosphere Using Coupled Hydrometeorological Simulations Over the Rocky Mountain Headwaters. Issue 17 (3rd September 2018) - Forrester, Mary M.; Maxwell, Reed M.; Bearup, Lindsay A.; Gochis, David J.
Abstract: The mountain pine beetle (MPB) has dramatically influenced high‐elevation pine forests of western North America, with recent infestations causing millions of acres of forest mortality and basal area loss. While ecohydrologic implications of infestation have been studied extensively in recent years, few have explored atmospheric feedbacks of widespread canopy transpiration loss or the potential role of groundwater to amplify or mitigate changes to land energy. This work presents bedrock‐to‐atmosphere simulations of coupled meteorological and hydrologic states over the Colorado headwaters. Analyses compare configurations with (1) default land surface parameters and (2) disturbance simulations with adjusted transpiration parameters in infested cells. An analysis of variance was conducted to identify regions of significant response to mountain pine beetle. Changes to increased soil moisture and Bowen ratios were found to be statistically significant in MPB‐infested areas and in nonlocal valleys, while planetary boundary layer (PBL) response was significant only in high elevations of the headwaters watershed. Temperature‐humidity covariance was evaluated using mixing diagrams; the results suggest that increased surface Bowen ratios from MPB could affect entrainment of dry air from the troposphere. The PBL is hotter, drier, and higher under infested forest conditions, which could have implications to atmosphere‐vegetation feedbacks and forest drought stress. Finally, land‐atmosphere coupling was sensitive to antecedent subsurface moisture. Regions with shallow water tables exhibit greater magnitude response to MPB at the surface and in the PBL, a finding that has repercussions for ecosystem resilience and hydrologic representation in meteorological modeling. Plain Language Summary: The mountain pine beetle (MPB), a species of bark beetle native to North America, has infested pine forests in the Rocky Mountains for the past two decades in an unprecedented epidemic. Millions of acres of high‐elevation lodgepole and ponderosa have died, and scientists are understandably interested in ecohydrologic implications. With canopy death comes increased soil moisture, surface temperature, and decreased transpiration, but few have investigated the possible atmospheric feedbacks from this forest disturbance. In this study, we use a hydrometeorological model to simulate the impact of MPB from the subsurface to the atmosphere. Model results show that infested regions experience decreased evaporative energy and higher surface temperatures, which affects the development of the planetary boundary layer (PBL), the highest point of the atmosphere still influenced by surface roughness. The diurnal evolution of the PBL is sensitive to moisture in the subsurface and surface vegetation. Our results show that regions with shallower water tables responded to simulated forest mortality with greater intensity. This means that ecohydrologic sensitivity to disturbance depends heavily on antecedent available moisture, a finding that can have implications to ecosystem health, resilience, and susceptibility to future land disturbance events. Key Points: Widespread forest mortality impacts the development of moisture and energy throughout the convective boundary layer Ensemble methods are necessary to appropriately quantify the likelihood of atmospheric response to land disturbance Depth to water table controls the magnitude of disturbance‐induced response in surface energy and lower atmosphere